Організація структурної корекції промислових підприємств - Ротанов, Г.М. (Культура народов Причерноморья, 2014)
У статті розроблено теоретичні і методичні положення, наукові та практичні рекомендації
щодо ефективної організації структурної корекції промислового виробництва на подальшу перспективу. В статье разработаны теоретические и методические положения, научные и
практические рекомендации по эффективной организации структурной коррекции промышленного
производства на дальнейшую перспективу. The theoretical and methodical positions, scientific and practical recommendations on the effective
organization of structural correction of industrial production on the further prospect are developed.
An analysis of structural changes in industrial production is based on the structural transformation ratio. The
calculation of this ratio by sectoral structure of industry allows to evaluate structural changes in dynamics, its
vector and make a conclusion about the optimality of the transformation processes.
It’s expedient to form the high–tech industrial structure on the basis of innovational policy. Comparison of
sectoral structural changes with industrial production technology allows to state the abrupt decline in advanced
technological modes of production of industrial products.
Institutional changes in industrial production take place in conditions of instability, and crises alter the general
meaning of the many changes, distorting their progress and impact. Problems concerning creating a critical
mass of market institutions are related to lack of coordination of structural reforms policy and change of
ownership. That odds with international experience of transformation (dispersion of ownership among small
shareholders, the lack of a strategic investor, a monopoly on the commodity markets, and the lack of
development of small business).